Evaluation of primary care: The "Primary Care Assessment Tools - Facility version" for the Spanish health system Evaluación de la atención primaria de salud: Primary Care Assessment Tools - Facility version para el sistema de salud español - M. Isabel Pasarín; Silvina Berra; Angelina González; Andreu Segura; Cristian Tebé; Anna García-Altés; Inma Vallverdú; Barbara Starfield (Elsevier, 2013)
Objective: To obtain versions of the Primary Care Assessment Tools (PCAT)-Facility version to evaluate primary care (PC) in the Spanish context, and to analyze its feasibility, reliability and validity. Methods: Cultural adaptation was performed through the use of forward and backward translations into Spanish and Catalan, observations and opinions of a panel of experts, and cognitive interviews with target users (PC team managers). A pilot phase was carried out in a sample of 130 managers of PC teams in Catalonia. A post-test questionnaire was sent 4-5 months later to all 194 managers of PC teams in the Barcelona health region. Analysis of metric properties included: 1) description of items and verification of Likert assumptions, since domain scores are obtained by summing item scores; 2) reliability analysis (Cronbach's alpha coefficient, Pearson's correlation coefficient, test-retest analysis); and 3) validity analysis (expert panel, cognitive interviews, and convergent and discriminant validity). Results: Substantial adaptation was required for the accessory section of the questionnaire, but less was required in PC domain measurements. Items were added to the comprehensiveness domain to reflect services usually available in Spain. The lowest Cronbach's alpha scores were found for Access (0.62) and Coordination (0.59 and 0.65), while values were >0.70 for the remaining domains. Conclusion: The Spanish version of the PCAT-Facility questionnaire is now available and shows adequate reliability and validity. The Spanish PCAT version will facilitate national and international comparisons of PC and analysis of the determinants of quality of service provision. Objetivo: Obtener versiones del Primary Care Assessment Tools-Facility version como herramienta de evaluación de la atención primaria (AP) para la aplicación en el contexto español, y analizar su fiabilidad y validez. Métodos: Se realizó una adaptación cultural con traducciones y retrotraducciones al español y al catalán, observaciones y opiniones de un panel de expertos y entrevistas cognitivas con usuarios finales (directivos del equipo de AP). Se realizó una fase piloto con una muestra de 130 directivos de AP de Cataluña. Una versión final se envió 4-5 meses después a los 194 directivos de los equipos de la región sanitaria de Barcelona. El análisis de las propiedades métricas incluyó: 1) descripción de ítems y verificación de las asunciones de la escala Likert, porque las puntuaciones de los dominios se obtienen sumando los ítems; 2) análisis de fiabilidad (alfa de Cronbach, coeficiente de correlación de Pearson, análisis test-retest); y 3) análisis de validez (panel de expertos, entrevistas cognitivas, validez convergente y discriminante). Resultados: Se requirió una importante adaptación de las secciones accesorias del cuestionario, pero no en las de los dominios de AP. Se añadieron ítems en la dimensión de globalidad. Las menores puntuaciones del alfa de Cronbach se encontraron en acceso (0,62) y coordinación (0,59 y 0,65); el resto de los dominios tuvieron valores > 0,70. Conclusión: Disponemos de una versión española del PCAT - Equipo de Atención Primaria con unas adecuadas fiabilidad y validez, que facilitará comparaciones nacionales e internacionales, y el análisis de los determinantes de una provisión de servicios de calidad.